Pengaruh Pertumbuhan Ekonomi, Jumlah Penduduk, Penanaman Modal Negeri Terhadap Pengangguran Di Indonesia Tahun 2015-2022 - Restianjani, Aiswara Arasy; Widyawati, Retno Febriyastuti (Economie: Jurnal Ilmu Ekonomi, 2025)
The purpose of this written research is to examine the impact of economic expansion, unemployment rates, and income inequality on the unemployment rate in Indonesia between 2015 and 2022. Secondary data used comes from various sources, including the Central Statistics Agency (BPS). The data used in this written research covers the years 2015–2022, with most of the data coming from the Indonesian Central Statistics Agency (BPS) and related books and journals. Regions or places with the highest percentage values of unemployment variables in Indonesia were selected using purposive sampling techniques, documentation techniques, and library research methods. The dependent variable in this written research is unemployment, while the independent variables are economic growth, poverty, and income inequality. The panel data used in this written research is a combination of cross-sectional and time series data. The observation size of this study is 72 and covers nine provinces with high unemployment rates over a period of eight years, namely 2015 to 2022. The provinces with the highest unemployment rates are Aceh, Riau Islands, West Sumatra, Banten, DKI Jakarta, West Java, North Sulawesi, Maluku, and West Papua. In written research, the research hypothesis is tested using the panel data regression analysis method. The Cammon Effect Model is proven to be the most effective model for written research, according to the results of the analysis. From 2015 to 2022, income inequality has a positive but insignificant effect on unemployment, poverty has a positive but insignificant effect, and economic growth has a negative and significant effect on unemployment in Indonesia.